2018
DOI: 10.1016/j.otsr.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Functional assessment of transplantar nailing for ankle fracture in the elderly: 48 weeks’ prospective follow-up of 14 patients

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Since 2005, 10 studies have been published on the treatment of these fractures with retrograde TTC nailing (Table 4). Most of these studies reported satisfactory functional results and low complication rates (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . In 2005, Lemon et al (9) published the first article on this technique: a case series of 12 patients (mean age, 84 years; follow-up, 67 weeks), achieving good functional results and early full weight bearing in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2005, 10 studies have been published on the treatment of these fractures with retrograde TTC nailing (Table 4). Most of these studies reported satisfactory functional results and low complication rates (9)(10)(11)(12)(13)(14)(15)(16)(17)(18) . In 2005, Lemon et al (9) published the first article on this technique: a case series of 12 patients (mean age, 84 years; follow-up, 67 weeks), achieving good functional results and early full weight bearing in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results were good, especially the low rate of wound complications and early recovery. In the same year, Persigant et al (17) published the results of a series of 14 patients treated with a retrograde femoral nail and immediate weight bearing, with a mean follow-up of 12 months. O´Daly 2010 (11) RT The authors reported satisfactory functional results, fracture union, and only 1 major complication (deep infection requiring nail removal).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persigant et al 48 prospectively evaluated 14 patients (mean age 79.6 years) who were treated with retrograde trans-plantar intramedullary nailing (TIMN). Ten of 14 patients were followed up for 48 weeks.…”
Section: Fibula Nail There Are Only Two Publications [Tablementioning
confidence: 99%
“…Acute tibiotalocalcaneal (TTC) nailing has been used to treat osteoporotic ankle fractures with good results since 2005 ( 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ), especially in frail patients, and, although several risk factors have been described in the literature as predictors of adverse effects after ankle ORIF ( 12 ), no specific inclusion criteria have been identified to opt for this surgical treatment.…”
Section: Introductionmentioning
confidence: 99%